A forensic visual aid: Traces versus knowledge. Issue 6 (November 2018) - van Beek, Harm
Abstract: In this paper, I introduce the Forensic Field Map (FFM) that provides a two-dimensional view on the forensic field. This field is by definition very broad, encompassing a wide range of scientific areas and activities. The forensic work that supports solving criminal cases ranges from recognizing and preserving traces at crime scenes to explaining forensic results as expert witness in court. This goes hand in hand with the development of scientifically based methods and tooling as well as legal, forensic and laboratory procedures. Although the FFM came into being while developing a (visual) framework for digital forensic investigations, the framework turned out to be generically applicable to other forensic disciplines. Graphical abstract: Highlights: The Forensic Field Map (FFM) serves as visual brainstorming aid to discuss the forensic field. The FFM is generically applicable to forensic disciplines, including cyber forensics. The FFM provides a two-dimensional view on the forensic field. The first dimension is derived by from the objects under investigation (traces). The second dimension is defined by the knowledge needed for processing the objects.